Understanding the Pathophysiology of Spinal Muscular Atrophy Skeletal Muscle - Boyer, Justin (Université d'Ottawa / University of Ottawa, 2013)
The disruption of the survival motor neuron (SMN1) gene leads to the children’s genetic disease spinal muscular atrophy (SMA). SMA is characterized by the degeneration of α-motor neurons and skeletal muscle atrophy. Although SMA is primarily considered a motor neuron disease, the involvement of muscle in its pathophysiology has not been ruled out. To gain a better understanding of the involvement of skeletal muscle pathophysiology in SMA, we have developed three aims: to identify cell-specific Smn-interacting proteins, to characterize postnatal skeletal muscle development in mouse models of SMA, and to assess the functional capacity of muscles from SMA model mice. We have used tandem affinity purification to discover Smn interacting partners in disease relevant cell types. We have identified novel cell-specific Smn interacting proteins of which we have validated myosin regulatory light chain as a muscle-specific Smn associated protein in vivo. We have taken advantage of two different mouse models of SMA, the severe Smn-/-;SMN2 mouse and the less severe Smn2B/- mouse, to study the postnatal development of skeletal muscle. Primary myoblasts from Smn2B/- mice demonstrate delayed myotube fusion and aberrant expression of the myogenic program. In addition, the expression of myogenic proteins was delayed in muscles from severe Smn-/-;SMN2 and less severe Smn2B/- SMA model mice. Muscle denervation and degeneration, however, are not the cause of the aberrant myogenic program. At the functional level, we demonstrate a significant decrease in force production in pre-symptomatic Smn-/-;SMN2 and Smn2B/- mice indicating that muscle weakness is an early event in these mice. Immunoblot analyses from hindlimb skeletal muscle samples revealed aberrant levels of developmentally regulated proteins important for muscle function, which may impact muscle force production in skeletal muscle of SMA model mice. The present study demonstrates early and profound intrinsic muscle weakness and aberrant expression of muscle proteins in mouse models of SMA, thus demonstrating how muscle defects can contribute to the disease phenotype independently of and in addition to that caused by motor neuron pathology.
Keywords: Spinal muscular atrophy; myogenesis; skeletal muscle